Development of an analytical method for the determination of low-level of dioxin and furans in marine and freshwater species - P-L Cloutier; F. Fortin; M. Fournier; P. Brousseau; P.-É. Groleau; M. Desrosiers (MDPI AG, 2014)
Not available